-7y+20=6y-6

Simple and best practice solution for -7y+20=6y-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7y+20=6y-6 equation:


Simplifying
-7y + 20 = 6y + -6

Reorder the terms:
20 + -7y = 6y + -6

Reorder the terms:
20 + -7y = -6 + 6y

Solving
20 + -7y = -6 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
20 + -7y + -6y = -6 + 6y + -6y

Combine like terms: -7y + -6y = -13y
20 + -13y = -6 + 6y + -6y

Combine like terms: 6y + -6y = 0
20 + -13y = -6 + 0
20 + -13y = -6

Add '-20' to each side of the equation.
20 + -20 + -13y = -6 + -20

Combine like terms: 20 + -20 = 0
0 + -13y = -6 + -20
-13y = -6 + -20

Combine like terms: -6 + -20 = -26
-13y = -26

Divide each side by '-13'.
y = 2

Simplifying
y = 2

See similar equations:

| 4x+15-17=16 | | 6x/7=20/14 | | (1-w)(4w+6)=0 | | a=b/c | | 8-4t=6t-22 | | 7x+4=24 | | 15s-8c=5c+48 | | 15X-19+4X+53-8X=2X-43+86+9X+35+-X | | 3m+24=7m | | -1/2m+8=10 | | 68=-2(m+5)+m | | (3x-8)(x+1)=0 | | 3z+24=-7z | | 5=5(x-4)+5-4x | | 4q+2=4 | | 68=-2 | | 1/7(x+2)=4 | | 0.4(0.71+6x)=3.2x | | a/15=b | | let(f)=5x^2-8x+3 | | 8X+59-5X=X-84+242+X | | 8+6+2x=8x | | 4t-2=1 | | x+2=4(4x-3) | | 2x=4-6 | | 3/4(x-16)=-51/4 | | 8p+8=3p-2 | | 6(c-9)=-30 | | 1x+3x+4=4x | | 5X-74+8X=7X+148+5X | | -13-9y=13 | | 4x^2-8x+6=0 |

Equations solver categories